Lingering Echoes - Smibert, Angie (Honesdale, Pennsylvania : Boyds Mills Press, an imprint of Highlights, 2019)
"In a southern Virginia coal-mining town in October 1942, Bone Phillips is learning to control her Gift: Bone can see the history of a significant object when she touches it. When her best friend, Will Kincaid, asks Bone to "read" the history of his daddy's jelly jar--the jelly jar that was buried alongside his father during the mine cave-in that killed him--Bone is afraid. Even before Bone touches it, she can feel that the jar has its own strange power. With her mother dead, her father gone to war, and Aunt Mattie's assault looming over Bone, she can't bear the idea of losing Will too. As Will's obsession with the jelly jar becomes dangerous, Bone struggles to understand the truth behind the jar and save him. Featuring a beautiful, compelling voice, this novel weaves a story of mystery, family, and ultimately, love."
Keywords: Psychic ability -- Fiction; Virginia -- Fiction; Paranormal fiction; Young adult fiction